(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Published information may lose its relevance if there is undue delay in it being reported. However, around the world, delay in the auditing of financial statements have been identified as leading to an overall delay in their publication. The study investigates the effect of firm attributes on financial reporting timeliness of the eleven (11) listed oil and gas firms on the Nigerian Stock Exchange for the period 2011 to 2020. Sample of eight (8) companies were selected using purposive sampling technique after applying a single filter. The study used Ex-post facto research design. The variables considered were firm age, firm size, leverage and profitability. Financial Reporting timeliness was measured using audit report lag. Panel data were collected from the annual reports and accounts of the selected firms. The multiple regression analysis technique was used to analyse the data. The result of the study indicates that firm age, firm size and profitability significantly affect financial reporting timeliness while leverage does not influence financial reporting timeliness. Therefore, the study concludes that firm attributes especially firm age and profitability are good predictors of financial reporting timeliness. The study recommends that firms should grow their assets, strive to make profit and incur less debt as these factors are very important for investment and other decision purposes by the users of the information.